Determination of temporary dye Basic Red 51 in commercial hair dye, river water and wastewater from hairdressing salon using graphite-epoxy composite electrode modified with magnetic nanoparticles - Corrêa, Gláucia Tinoco [UNESP]; Souza, João Carlos de [UNESP]; Silva, João Pedro [UNESP]; Pividori, Maria Isabel; Zanoni, Maria Valnice Boldrin [UNESP] (Elsevier, 2020)
The present work reports the development of a simple, fast and inexpensive method for the determination of Basic Red 51 (BR 51) dye, known to be widely employed in comercial formulations of temporary dyes. The method involved the use of graphite-epoxy magnetic composite electrode (GEMCE) modified by carboxyl-functionalyzed magnetic nanoparticles (CFMNs) for the pre-concentration of the dye aiming at increasing the electrode sensitivity through the application of square wave voltammetry. The pre-concentration of BR 51 occurs via strong interaction between charged imidazole group present in the dye and the carboxyl group in the magnetic nanoparticles. This reaction is the basis for BR 51 determination through a well-defined peak at +0.89 V vs. Ag/AgCl, which is attributed to the oxidation of tertiary amine after the transfer of one electron and one proton. Under optimized conditions, which consisted of 30 sec. exposure of the GEMCE/CFMNs to BR 51 dye immersed in phosphate buffer (pH 7.0), an analytical curve was constructed in the concentration range of 1.50 × 10−6 mol L−1 to 5.50 × 10−5 mol L−1 using square wave voltammetry (SWV). The limits of detection and quantification obtained were 1.19 × 10−7 and 3.97 × 10−7 mol L−1, respectively. The proposed method was successfully applied for the determination of BR 51 dye in samples of commercial hair dye, wastewater from hairdressing salon, and river water, and was validated using high performance chromatography coupled to diode array detector (HPLC-DAD).
Keywords: Basic Red 51 determination; Electroanalysis of hair dyes; Hair dye analysis in wastewater; Magnetic nanoparticles modified electrode